Porous positive electrode plate of lead-acid storage battery and preparation method of porous positive electrode plate
By adding borate and SnO2/MIL-88-FeaCob-Bc composite material to the positive electrode plate of the lead-acid battery, the problems of low energy density and slow charge and discharge of existing lead-acid batteries are solved, and higher porosity and conductivity are achieved, and the service life of the battery is extended.
Patent Information
- Application Number
- CN202510102180.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-29
AI Technical Summary
Existing lead-acid batteries have defects in volume, power storage and charging time, resulting in low energy density and slow charging and discharge, limiting their application range.
By adding borate and SnO2/MIL-88-FeaCob-Bc composite material to the positive electrode plate of the lead-acid battery, the porosity and conductivity of the electrode plate are adjusted to improve battery performance.
It significantly improves the porosity of the electrode plate and the charging and discharging efficiency of the battery, extends the cycle life of the battery, and improves the capacity and performance of the battery.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lead-acid batteries, and in particular relates to a porous positive electrode plate of a lead-acid battery and a preparation method thereof. Background Art
[0002] In order to ensure the strength of the plates and avoid breakage and the fall of the attached lead paste, the current lead-acid batteries are forced to thicken the positive and negative plates and solidify the active materials. The thickening of the plates also requires an increase in the amount of sulfuric acid injected into the medium, which in turn leads to the thickening of the glass fiber separators. The thickening of the separators will increase the relative distance between the plates. In addition, the poor activity of the coating materials at both poles causes the poor conductivity of the plate materials. These are the reasons for the low energy density and slow charging and discharging of lead-acid batteries.
[0003] The preparation of the positive plate of the battery is done by weighing the lead powder, formula material, short fiber, water, and acid, and then adding them to the vacuum paste machine in turn. The vacuum paste machine is dry-mixed and mixed evenly. The mixing time is controlled during the mixing process to ensure uniform mixing and to ensure that the auxiliary materials with different specific gravities cannot be stratified. Then water is added for wet mixing. After mixing, sulfuric acid is added 5-6 times. The sulfuric acid reacts to raise the temperature of the lead paste, and the lead oxide reacts to produce basic lead sulfate. Finally, the temperature of the lead paste rises to above 70°C, and the vacuum paste machine is turned on synchronously to evacuate. The temperature of the lead paste is adjusted and controlled by the vacuum degree. It cannot be too high, and the vacuum degree of the paste is increased in the later stage, so that the lead paste is cooled quickly, and the condensed water is withdrawn synchronously to ensure the moisture content of the lead paste. After the prepared lead paste is made into a plate and cured and dried, the water evaporates to form a certain porosity, which has a certain influence on the capacity and performance of the plate.
[0004] The patent application with publication number CN 103227316 A discloses a positive electrode plate of a lead-acid battery, including a positive grid and an active material coated on the positive grid, wherein the active material comprises the following components in weight: 1000 parts of lead dioxide; 5-50 parts of bismuth oxide; 10-50 parts of graphite; 0.1-1 parts of composite rare earth; 0-20 parts of active additives; wherein the composite rare earth contains the following components by mass fraction: cerium Ce: 52-67%, yttrium Y: 12-22%, neodymium Nd: 10-20%; and unavoidable impurities. Compared with ordinary lead-tin alloy battery grids, this application has higher corrosion resistance and deformation performance, high specific gravity capacity, and still has good battery capacity after multiple deep charge and discharge cycles, so it has a longer life.
[0005] However, the lead-acid batteries in the prior art have certain defects in terms of volume, storage capacity, charging time, etc., which limit the application scope of the lead-acid batteries. Summary of the invention
[0006] The object of the present invention is to provide a lead-acid battery porous positive electrode plate and a preparation method thereof, so as to increase the plate porosity and improve the battery performance.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A porous positive electrode plate for a lead-acid battery, comprising a positive electrode grid and a positive electrode lead paste;
[0009] The positive plate lead paste comprises, by weight, 100-120 parts of lead powder, 0.5-1 parts of glass fiber, 10-15 parts of deionized water, 15-20 parts of dilute sulfuric acid, 5-15 parts of borate and 2-4 parts of SnO2 / MIL-88-Fe a Co b -B c Composite materials.
[0010] Furthermore, the borate includes one or a combination of sodium borate, aluminum borate, ammonium borate and calcium borate; and the mass fraction of the dilute sulfuric acid is 20%-40%.
[0011] Furthermore, the SnO2 / MIL-88-Fe a Co b -B c The composite material is prepared by the following steps:
[0012] Ferric chloride, cobalt dichloride and phthalic acid were uniformly dispersed in pure water, hydrothermally reacted, centrifuged, washed and dried to obtain MIL-88-Fe a Co b ; MIL-88-Fe a Co b and H3BO3 were dispersed in deionized water, heated, centrifuged, washed and dried to obtain MIL-88-Fe a Co b -B c ;
[0013] MIL-88-Fe a Co b -B c Evenly mixed with SnCl2·2H2O, vacuum dried, washed, placed in a humid environment; calcined to obtain SnO2 / MIL-88-Fe a Co b -B c Composite materials.
[0014] Furthermore, the molar ratio of the ferric chloride, cobalt dichloride and phthalic acid is (8-2): (1-1.5): (1-2).
[0015] Furthermore, the MIL-88-Fea Co b , the dosage ratio of boric acid and deionized water is (200-300) mg: (16-32) g: (15-30) g.
[0016] Furthermore, the hydrothermal reaction is carried out at 120-150° C. for 12-14 hours; and the heating is carried out at 80-90° C. for 1-2 hours.
[0017] Furthermore, the MIL-88-Fe a Co b -B c The usage ratio of SnCl2·2H2O is (1-1.5)g:(8-12)g.
[0018] Furthermore, the vacuum drying is drying under vacuum conditions of 50-60° C. for 12-14 hours; the washing is washing with anhydrous ethanol; and the placing in a humid environment is placing in an environment with room temperature and humidity ≥ 95% for 12-14 hours.
[0019] Furthermore, the calcination is carried out at 500-600° C. for 5-6 hours.
[0020] A method for preparing a porous positive electrode plate of a lead-acid battery comprises the following steps:
[0021] Lead powder, glass fiber, borate and SnO2 / MIL-88-Fe a Co b -B c The composite material is mixed evenly to obtain a mixture; deionized water is added to the mixture, stirred evenly, and then dilute sulfuric acid is added and stirred evenly to obtain a positive electrode lead paste; the lead paste is evenly scraped on the grid, cured, and dried to obtain a positive electrode plate.
[0022] Furthermore, the curing is performed at 50-80° C. for 18-24 hours; and the drying is performed at 60-100° C. for 18-24 hours.
[0023] Beneficial effects of the present invention:
[0024] (1) The present invention provides a porous positive electrode plate for a lead-acid battery and a preparation method thereof. By adding borate, the boric acid is decomposed and volatilized at high temperature when the plate is cured and dried, which can play a role in forming pores in the plate. The porosity of the plate can be significantly improved, thereby improving battery performance.
[0025] (2) SnO2 / MIL-88-Fe a Co b -B cComposite materials, firstly, cobalt and boron are introduced into the MOF structure by hybridization, which adjusts the charge arrangement mode of MIL-88-Fe, enhances its conductivity, and accelerates the formation of key active intermediate *N2H, thereby improving battery performance; however, there will be structural instability problems, and SnO2 will be in the MIL-88-Fe during the formation process. a Co b -B c A Sn(OH)4 coating layer is formed on the positive electrode to stabilize its structure. On the other hand, Sn can enhance the conductivity of the positive electrode plate and improve the charge and discharge efficiency of the battery.
[0026] (3) In the method for preparing a porous positive electrode plate of a lead-acid battery provided by the present invention, the added borate and SnO2 / MIL-88-Fe a Co b -B c The composite materials have a synergistic effect. The borate in the lead paste component can reduce the hydrolysis of boron in the boron-containing MOF composite material and improve the stability of the composite material. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] This embodiment provides a porous positive electrode plate for a lead-acid battery, which is prepared by the following steps:
[0030] S1. Disperse 0.6 mol ferric chloride, 0.1 mol cobalt dichloride and 0.15 mol phthalic acid uniformly in pure water, react at 150°C for 12 h, centrifuge, wash and dry to obtain MIL-88-Fe a Co b ; 250mg MIL-88-Fe a Co b and 24gH3BO3 were dispersed in 25mL deionized water, heated at 80℃ for 2h, centrifuged, washed and dried to obtain MIL-88-Fe a Co b -B c ;
[0031] 1g MIL-88-Fe a Co b -B cIt was uniformly mixed with 10g SnCl2·2H2O, dried under vacuum at 60℃ for 12h, washed with anhydrous ethanol, placed in an air environment at room temperature and humidity ≥95% for 12h; calcined at 500℃ for 6h to obtain SnO2 / MIL-88-Fe a Co b -B c Composite materials;
[0032] S2, 100g lead powder, 0.8g glass fiber, 10g sodium borate and 3g SnO2 / MIL-88-Fe a Co b -B c The composite material is mixed evenly to obtain a mixture; 12 g of deionized water is added to the mixture, stirred evenly, and then 18 g of dilute sulfuric acid with a mass fraction of 30% is added, stirred evenly, to obtain a positive electrode lead paste; the lead paste is evenly scraped on the grid, cured at 60° C. for 24 hours, and dried at 80° C. for 24 hours to obtain a positive electrode plate.
[0033] Example 2
[0034] The difference between this embodiment and embodiment 1 is that "10g sodium borate and 3g SnO2 / MIL-88-Fe a Co b -B c Composite material" was changed to "15g sodium borate and 2g SnO2 / MIL-88-Fe a Co b -B c Composite materials", S2 specific implementation steps are:
[0035] S2, 100g lead powder, 0.8g glass fiber, 15g sodium borate and 2g SnO2 / MIL-88-Fe a Co b -B c The composite material is mixed evenly to obtain a mixture; 12 g of deionized water is added to the mixture, stirred evenly, and then 18 g of dilute sulfuric acid with a mass fraction of 30% is added, stirred evenly, to obtain a positive electrode lead paste; the lead paste is evenly scraped on the grid, cured at 60° C. for 24 hours, and dried at 80° C. for 24 hours to obtain a positive electrode plate.
[0036] The remaining raw materials and preparation process remain the same as in Example 1.
[0037] Example 3
[0038] The difference between this embodiment and embodiment 1 is that "10g sodium borate and 3g SnO2 / MIL-88-Fe a Co b -Bc Composite material" was changed to "5g sodium borate and 4g SnO2 / MIL-88-Fe a Co b -B c Composite materials", S2 specific implementation steps are:
[0039] S2, 100g lead powder, 0.8g glass fiber, 5g sodium borate and 4g SnO2 / MIL-88-Fe a Co b -B c The composite material is mixed evenly to obtain a mixture; 12 g of deionized water is added to the mixture, stirred evenly, and then 18 g of dilute sulfuric acid with a mass fraction of 30% is added, stirred evenly, to obtain a positive electrode lead paste; the lead paste is evenly scraped on the grid, cured at 60° C. for 24 hours, and dried at 80° C. for 24 hours to obtain a positive electrode plate.
[0040] The remaining raw materials and preparation process remain the same as in Example 1.
[0041] Example 4
[0042] The difference between this embodiment and embodiment 1 is that the "1g MIL-88-Fe a Co b -B c and 10g SnCl2·2H2O" was changed to "1.5g MIL-88-Fe a Co b -B c and 8g SnCl2·2H2O”, S1 specific implementation steps are:
[0043] S1. Disperse 0.6 mol ferric chloride, 0.1 mol cobalt dichloride and 0.15 mol phthalic acid uniformly in pure water, react at 150°C for 12 h, centrifuge, wash and dry to obtain MIL-88-Fe a Co b ; 250mg MIL-88-Fe a Co b and 24gH3BO3 were dispersed in 25mL deionized water, heated at 80℃ for 2h, centrifuged, washed and dried to obtain MIL-88-Fe a Co b -B c ;
[0044] 1.5g MIL-88-Fe a Co b -B cIt was uniformly mixed with 8g SnCl2·2H2O, dried under vacuum at 60℃ for 12h, washed with anhydrous ethanol, placed in an air environment at room temperature and humidity ≥95% for 12h; calcined at 500℃ for 6h to obtain SnO2 / MIL-88-Fe a Co b -B c Composite materials;
[0045] The remaining raw materials and preparation process remain the same as in Example 1.
[0046] Example 5
[0047] The difference between this embodiment and embodiment 1 is that the "250 mg MIL-88-Fe a Co b and 24g H3BO3" to "300mg MIL-88-Fe a Co b and 16g H3BO3”, S1 specific implementation steps are:
[0048] S1. Disperse 0.6 mol ferric chloride, 0.1 mol cobalt dichloride and 0.15 mol phthalic acid uniformly in pure water, react at 150°C for 12 h, centrifuge, wash and dry to obtain MIL-88-Fe a Co b ; 300mg MIL-88-Fe a Co b and 16gH3BO3 were dispersed in 25mL deionized water, heated at 80℃ for 2h, centrifuged, washed and dried to obtain MIL-88-Fe a Co b -B c ;
[0049] 1g MIL-88-Fe a Co b -B c It was uniformly mixed with 10g SnCl2·2H2O, dried under vacuum at 60℃ for 12h, washed with anhydrous ethanol, placed in an air environment at room temperature and humidity ≥95% for 12h; calcined at 500℃ for 6h to obtain SnO2 / MIL-88-Fe a Co b -B c Composite materials;
[0050] The remaining raw materials and preparation process remain the same as in Example 1.
[0051] Example 6
[0052] The difference between this embodiment and embodiment 1 is that the "250 mg MIL-88-Fe a Co b and 24g H3BO3" to "200mg MIL-88-Fe a Co b and 32g H3BO3”, S1 specific implementation steps are:
[0053] S1. Disperse 0.6 mol ferric chloride, 0.1 mol cobalt dichloride and 0.15 mol phthalic acid uniformly in pure water, react at 150°C for 12 h, centrifuge, wash and dry to obtain MIL-88-Fe a Co b ; 200mg MIL-88-Fe a Co b and 32gH3BO3 were dispersed in 25mL deionized water, heated at 80℃ for 2h, centrifuged, washed and dried to obtain MIL-88-Fe a Co b -B c ;
[0054] 1g MIL-88-Fe a Co b -B c It was uniformly mixed with 10g SnCl2·2H2O, dried under vacuum at 60℃ for 12h, washed with anhydrous ethanol, placed in an air environment at room temperature and humidity ≥95% for 12h; calcined at 500℃ for 6h to obtain SnO2 / MIL-88-Fe a Co b -B c Composite materials;
[0055] The remaining raw materials and preparation process remain the same as in Example 1.
[0056] Example 7
[0057] Compared with Example 1, the difference between this example is that "10 g sodium borate" in S2 is changed to "14.5 g aluminum borate", and the specific implementation steps of S2 are:
[0058] S2, 100g lead powder, 0.8g glass fiber, 14.5g aluminum borate and 3g SnO2 / MIL-88-Fe a Co b -B cThe composite material is mixed evenly to obtain a mixture; 12 g of deionized water is added to the mixture, stirred evenly, and then 18 g of dilute sulfuric acid with a mass fraction of 30% is added, stirred evenly, to obtain a positive electrode lead paste; the lead paste is evenly scraped on the grid, cured at 60° C. for 24 hours, and dried at 80° C. for 24 hours to obtain a positive electrode plate.
[0059] The remaining raw materials and preparation process remain the same as in Example 1.
[0060] Comparative Example 1
[0061] Compared with Example 1, this comparative example differs in that no borate is added, and the specific implementation steps of S2 are:
[0062] S2, 110g lead powder, 0.8g glass fiber and 3g SnO2 / MIL-88-Fe a Co b -B c The composite material is mixed evenly to obtain a mixture; 12 g of deionized water is added to the mixture, stirred evenly, and then 18 g of dilute sulfuric acid with a mass fraction of 30% is added, stirred evenly, to obtain a positive electrode lead paste; the lead paste is evenly scraped on the grid, cured at 60° C. for 24 hours, and dried at 80° C. for 24 hours to obtain a positive electrode plate.
[0063] The remaining raw materials and preparation process remain the same as in Example 1.
[0064] Comparative Example 2
[0065] Compared with Example 1, this comparative example is different in that SnO2 / MIL-88-Fe a Co b -B c Composite material, S2 specific implementation steps are:
[0066] S2. Mix 103g of lead powder, 0.8g of glass fiber and 10g of sodium borate to obtain a mixture; add 12g of deionized water to the mixture, stir evenly, then add 18g of dilute sulfuric acid with a mass fraction of 30%, stir evenly to obtain a positive plate lead paste; scrape the lead paste evenly on the grid, cure it at 60°C for 24h, and dry it at 80°C for 24h to obtain a positive electrode plate.
[0067] The remaining raw materials and preparation process remain the same as in Example 1.
[0068] Comparative Example 3
[0069] Compared with Example 1, this comparative example is different in that SnO2 coating and doping are not performed, and the specific implementation steps are as follows:
[0070] S1. Disperse 0.6 mol ferric chloride, 0.1 mol cobalt dichloride and 0.15 mol phthalic acid uniformly in pure water, react at 150°C for 12 h, centrifuge, wash and dry to obtain MIL-88-Fe a Co b ; 250mg MIL-88-Fe a Co b and 24gH3BO3 were dispersed in 25mL deionized water, heated at 80℃ for 2h, centrifuged, washed and dried to obtain MIL-88-Fe a Co b -B c ;
[0071] S2, 100g lead powder, 0.8g glass fiber, 10g sodium borate and 3g MIL-88-Fe a Co b -B c The composite material is mixed evenly to obtain a mixture; 12 g of deionized water is added to the mixture, stirred evenly, and then 18 g of dilute sulfuric acid with a mass fraction of 30% is added, stirred evenly, to obtain a positive electrode lead paste; the lead paste is evenly scraped on the grid, cured at 60° C. for 24 hours, and dried at 80° C. for 24 hours to obtain a positive electrode plate.
[0072] The remaining raw materials and preparation process remain the same as in Example 1.
[0073] Comparative Example 4
[0074] The difference between this comparative example and Example 1 is that SnO2 / MIL-88-Fe a Co b -B c Composite material and borate, S2 specific implementation steps are:
[0075] S2. Mix 113g of lead powder and 1g of glass fiber to obtain a mixture; add 12g of deionized water to the mixture, stir evenly, then add 18g of dilute sulfuric acid with a mass fraction of 30%, stir evenly to obtain a positive plate lead paste; scrape the lead paste evenly on the grid, cure it at 60°C for 24h, and dry it at 80°C for 24h to obtain a positive electrode plate.
[0076] The remaining raw materials and preparation process remain the same as in Example 1.
[0077] Performance Test:
[0078] The performance tests were performed on Examples 1 to 7 and Comparative Examples 1 to 4.
[0079] According to GB / T22199-2017, the positive electrode plates obtained in various embodiments and comparative examples of the present application were subjected to cycle life tests;
[0080] First, assemble the positive plates into a lead-acid battery. In an environment of 20°C, charge it at a constant voltage of 14.1V and a current limit of 75A for 16h, and then discharge it at a constant current of 50A to a termination voltage of 11.0V as one cycle. When the discharge capacity of the entire battery is less than 80% of the rated capacity, record the number of cycles.
[0081] The results are shown in Table 1:
[0082] Table 1
[0083] project Capacity(Ah) Cycle times (times) Example 1 17.1 281 Example 2 16.9 277 Example 3 16.6 273 Example 4 16.4 268 Example 5 16.0 263 Example 6 16.2 266 Example 7 16.5 271 Comparative Example 1 13.7 225 Comparative Example 2 14.3 236 Comparative Example 3 15.2 250 Comparative Example 4 12.5 220
[0084] It can be seen from the embodiments and comparative examples in combination with Table 1 that the lead-acid battery assembled from the positive plate prepared by the present invention has not only a long cycle life but also a large capacity under high current charge and discharge conditions. The only difference between Examples 2-7 and Example 1 is the raw material ratio or the change test of the raw materials within a reasonable range. From the results, the prepared lead-acid batteries have good performance and a long service life.
[0085] Compared with Example 1, the battery performance of Comparative Example 1 is reduced after no borate is added. This is because the borate decomposes and volatilizes when the plate is cured and dried, which can play a role in plate pore formation, increase the plate porosity, and thus improve the battery performance; Compared with Example 1, SnO2 / MIL-88-Fe a Co b -B c After the composite material, the battery capacity and cycle number decreased, which is because SnO2 / MIL-88-Fe a Co b -B c The composite material has the effect of enhancing its conductivity and accelerating the key active intermediate *N2H; Comparative Example 3 compared with Example 1 and Comparative Example 2 shows that the introduction of Sn can not only enhance the conductivity of the positive electrode plate and improve the charge and discharge efficiency of the battery, but also effectively improve the MIL-88-Fe a Co b -B c The stability of the battery is improved; the battery performance of Comparative Example 4 is greatly reduced compared with Comparative Examples 1-4 and Example 1, which just shows that the borate added in the present invention can not only improve the plate porosity, but also can improve the stability of the battery performance of the battery. a Co b -B cThe composite materials have a synergistic effect. The borate in the lead paste component can reduce the hydrolysis of boron in the boron-containing MOF composite material, and has the effect of improving the stability of the composite material.
[0086] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A porous positive electrode plate for a lead-acid battery, characterized in that: Including positive plate grid and positive plate lead paste; The positive plate lead paste comprises, by weight, 100-120 parts of lead powder, 0.5-1 parts of glass fiber, 10-15 parts of deionized water, 15-20 parts of dilute sulfuric acid, 5-15 parts of borate and 2-4 parts of SnO2 / MIL-88-Fe a Co b -B c Composite materials.
2. A lead-acid battery porous positive electrode plate according to claim 1, characterized in that: The borate comprises one or a combination of sodium borate, aluminum borate, ammonium borate and calcium borate; the mass fraction of the dilute sulfuric acid is 20%-40%.
3. A lead-acid battery porous positive electrode plate according to claim 1, characterized in that: The SnO2 / MIL-88-Fe a Co b -B c The composite material is prepared by the following steps: Ferric chloride, cobalt dichloride and phthalic acid were uniformly dispersed in pure water, hydrothermally reacted, centrifuged, washed and dried to obtain MIL-88-Fe a Co b ; MIL-88-Fe a Co b and H3BO3 were dispersed in deionized water, heated, centrifuged, washed and dried to obtain MIL-88-Fe a Co b -B c ; MIL-88-Fe a Co b -B c Evenly mixed with SnCl2·2H2O, vacuum dried, washed, placed in a humid environment; calcined to obtain SnO2 / MIL-88-Fe a Co b -B c Composite materials.
4. A lead-acid battery porous positive electrode plate according to claim 3, characterized in that: The molar ratio of the ferric chloride, cobalt dichloride and phthalic acid is (8-2): (1-1.5): (1-2).
5. A lead-acid battery porous positive electrode plate according to claim 3, characterized in that: The MIL-88-Fe a Co b , the dosage ratio of boric acid and deionized water is (200-300) mg: (16-32) g: (15-30) g.
6. A lead-acid battery porous positive electrode plate according to claim 3, characterized in that: The hydrothermal reaction is carried out at 120-150° C. for 12-14 hours; and the heating is carried out at 80-90° C. for 1-2 hours.
7. A lead-acid battery porous positive electrode plate according to claim 3, characterized in that: The MIL-88-Fe a Co b -B c The usage ratio of SnCl2·2H2O is (1-1.5)g:(8-12)g.
8. A lead-acid battery porous positive electrode plate according to claim 3, characterized in that: The vacuum drying is drying under vacuum conditions of 50-60° C. for 12-14 hours; the washing is washing with anhydrous ethanol; the placing in a humid environment is placing in an environment with room temperature and humidity ≥ 95% for 12-14 hours; the calcining is calcining at 500-600° C. for 5-6 hours.
9. A method for preparing a porous positive electrode plate for a lead-acid battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: Lead powder, glass fiber, borate and SnO2 / MIL-88-Fe a Co b -B c The composite material is mixed evenly to obtain a mixture; deionized water is added to the mixture, stirred evenly, and then dilute sulfuric acid is added and stirred evenly to obtain a positive electrode lead paste; the lead paste is evenly scraped on the grid, cured, and dried to obtain a positive electrode plate.
10. The method for preparing a porous positive electrode plate for a lead-acid battery according to claim 9, characterized in that: The curing is performed at 50-80° C. for 18-24 hours; and the drying is performed at 60-100° C. for 18-24 hours.
Citation Information
Patent Citations
Positive electrode plate of lead-acid battery and preparation method thereof
CN103227316A